Eletrocardiograma de baixo custo com análise de batimentos cardíacos utilizando Neuro-Fuzzy - Modenezi, Igor Kuczuk [UNESP] (2018)
Cardiovascular diseases are some of the main causes of death in the world, generating a great cost to the public coffers. On account of this, the early detection is essential, allowing for cheaper treatments. This is possible through an analysis using an electrocardiogram. In health centers, this equipment are usually older (utilizing pen and paper to do the readings) and require the presence of a cardiologist. One solution to this problem is the development of a low-cost electrocardiogram, using open source resources, such as Arduino and AD8232, and a Fuzzy controller, developed through ANFIS. In this work, it was only considered for analysis ischemia that generates heart arrhythmia. After the development of the model in Matlab, measurements were conducted using real equipment to prove the usage